The role of HPV16 regulatory region methylation in viral oncogenes E6 and E7 eхpression in primary cervical cancer lesions - P. M. Abramov; A. N. Katargin; M. D. Fedorova; N. P. Kisseljova; L. S. Pavlova; S. V. Vinokurova (Успехи молекулярной онкологии)
Background. Overexpression of the human papillomavirus oncogenes E6 and E7 is a major factor in initiation and progression of HPV-induced tumors. Inactivation of negative regulatory function of E2 protein – the main viral transcription and replication regulator – is considered to be an important mechanism leading to the viral oncogenes overexpression. It is known that the loss of E2 functions occurs due to disruption of E2 open reading frame during the viral DNA integration into a cell genome in a part of HPV-positive tumors. An alternative mechanism of E2 function blocking in tumors retained its expression can be methylation of the HPV regulatory region, since it is known that E2 is incapable to bind its methylated binding sites.The study objective is to analyze methylation of the HPV16 regulatory region and expression of the viral E6 and E7 oncogenes in E2 expressing or non-expressing clinical samples of cervical cancer.Results. It has been demonstrated that the level of the HPV16 URR methylation in E2-expressing lesions is significantly higher than that in non-expressing cervical cancer lesions. Demethylation of the HPV16 promoter in cervical cell line Caski is followed by decrease of the viral E6 и E7 oncogenes mRNA levels, supporting the hypothesis that methylation is necessary for effective E6 and E7 transcription and indicates on restitution of E2 regulatory function in E2-expressing cervical cancer cells.Conclusion. These data suggest that methylation of E2 binding sites in HPV16 regulatory region blocking E2 protein binding represents an important mechanism ensuring high level of the viral E6 and E7 oncogenes expression.